An Analysis of Students Prceptions of Pre-reading Activity on Reading Learning Process - rofika firdausi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The pre-reading activity steps before the reading text given to the students, which will help students understand the text easily. Students often lack vocabulary in their schemes or do not have enough vocabulary to read the text, so it makes them confused and they do not understand. Pre-reading activities can develop their vocabulary and at the same time, help them to read a comprehension and improve the achievement of reading. So, the learners will be more active in reading by having this kind of activity, and the reading lesson will be more interesting and will improve their reading achievement later on. This study aims to describe and explain how are student’s perception of pre-reading activity on student reading learning process at the third-semester student of the University of Islam Malang, and what kinds of pre-reading activity that is used by the teacher to student in teaching Reading. The research design of this study used the qualitative method, which belongs to descriptive research. The researcher conducted this research at the University of Islam Malang exactly the third-semester students English Department in Faculty and Teacher Training and Education. While the participants of this study was five students taken from every 4 classes, and two reading lecturers, the researcher decided to took the students which had A score in reading course in the previous semester to class A and D and the researcher took only 5 students. The teachers have interviewed by the researcher, namely teachers who have experience in teaching reading classes. As the instrument used two types of interview worksheets. The first for the teacher, and the second for the students. The interview worksheet for the teacher consists of sixteen questions related to what strategy used and related to a pre-reading activity used in the learning process. The interview worksheet for the students consists of 18 questions that are related to students' perception of pre-reading activity applied by the teacher. The interview used a smartphone voice recorder. The questions of the interview questions were made by the researcher.The result of this study showed that the students have positive perceptions and good opinions about pre-reading activity used in their reading learning process. the student's pre-reading activity is very useful for them to be more ready to receive was record the material. Also, pre-reading reading activity makes them curious about the text, interested and can motivate them to read the difficult text. Then, pre-reading activities can help them imagine the content of the text and remember their experiences related to the topic of the text. Also, the finding showed that brainstorming, discussions, skimming, scanning, KWL strategy, Pre-vocabulary were the varieties of Pre-reading activities and strategy Implemented on Third Semester Students in the Reading Learning process.Keywords: Students' Perception, Pre-Reading activity, and Students